ANALYSIS OF STRESS ELEMENTS IMPACT ON WORK-LIFE BALANCE WITH SIGNIFICANCE OF WORK FROM HOME CULTURE – A POST COVID-19 SCENARIO (Journal of Pharmaceutical Negative Results, 2023)
Human Rights are of fundamental significance for all human beings. The domestic violence and work-life balance are two vital elements during the Covid-19 pandemic. However, as a post-pandemic view, many multinational companies continued the work from home business model. The domestic violence because of work from home model boosted during the lockdowns but as a post pandemic scenario, this domestic violence is lowered. The reason behind this is the flexibility in work from home as well as space for every family member. This paper presents the post-pandemic analysis for human right violence and occupational stress levels.